2010
DOI: 10.1007/s11033-010-0221-0
|View full text |Cite
|
Sign up to set email alerts
|

GSTT1 and GSTM1 gene polymorphisms in European and African populations

Abstract: Glutathione S-transferases (GSTs) are a superfamily of detoxificant enzymes. Pharmacogenomic studies have revealed interethnic differences in GST allelic frequencies. This study is focused on GSTT1 (gene deletion, rs17850155, rs2234953, and rs11550605) and GSTM1 (gene deletion) gene frequency distributions in two population samples of Europe origin (Italy, n = 120; Spain, n = 94) and two population samples of Africa origin (Cameroon, n = 126; Ethiopia, n = 153). Detection of GSTT1 and GSTM1 null genotypes was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
45
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 32 publications
11
45
1
1
Order By: Relevance
“…The frequencies of GSTT1 deletion in our populations were higher than that described for Europeans, including British (18%) [20], French (16%) [21], German (13%) [22] and Austrian (20%) [23], as well as for other Middle Eastern populations, including Turks (17.3%) [24], and Iranians (21.2%) [25], but was significantly lower than SouthEast Asians, such as Chinese (56.5%) [26], Koreans (53.8%) [27] and Japanese (44%) [28]. The frequencies of GSTT1 null genotype in our Arab populations are similar to that of the sub-Saharan Africans: Zimbabweans (26%) [30], Gambians (37.1%) [31], Cameroonians (46.8%) [32] and Ivory Coast (33.1%) [33] (Table 2). The difference of GTSM1 and GSTT1 null alleles' frequency between our samples and those of others is attributed to their evolutionary histories, and also to selection arising from varied exposures to toxic substances.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The frequencies of GSTT1 deletion in our populations were higher than that described for Europeans, including British (18%) [20], French (16%) [21], German (13%) [22] and Austrian (20%) [23], as well as for other Middle Eastern populations, including Turks (17.3%) [24], and Iranians (21.2%) [25], but was significantly lower than SouthEast Asians, such as Chinese (56.5%) [26], Koreans (53.8%) [27] and Japanese (44%) [28]. The frequencies of GSTT1 null genotype in our Arab populations are similar to that of the sub-Saharan Africans: Zimbabweans (26%) [30], Gambians (37.1%) [31], Cameroonians (46.8%) [32] and Ivory Coast (33.1%) [33] (Table 2). The difference of GTSM1 and GSTT1 null alleles' frequency between our samples and those of others is attributed to their evolutionary histories, and also to selection arising from varied exposures to toxic substances.…”
Section: Discussionsupporting
confidence: 52%
“…Significant differences in GSTM1 null genotype distribution were seen with respect to Indians (20.7%) [29], and Africans, including Zimbabweans (24%) [30], Gambians (20.2%) [31], Cameroonians (27.8%) [32], and Ivory Coast (36.1%) [33] (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In another study involving a population from central Italy, the frequencies were found to be 50.4% and 16.7%, respectively (Table 3) [58] . The frequencies of the GSTM1 and GSTT1 null phenotypes in Italian population [57,58] are in line with those observed in Caucasian populations, 40% -65% and 10% -40%, respectively [57,90] .…”
supporting
confidence: 87%
“…In a study from a large sample of an Italian population, the frequencies of GSTM1 and GSTT1 null genotype were found to be 49.2% and 28.3%, respectively [57] . In another study involving a population from central Italy, the frequencies were found to be 50.4% and 16.7%, respectively (Table 3) [58] .…”
mentioning
confidence: 96%
“…The frequency of the GSTM1 null genotype in the present study was significantly higher than those in Asian populations, that is, Indian and Japanese (Kihara and Noda, 1999;Sharma et al, 2012) populations, and African populations, that is, Zimbabwean and Cameroonian populations (Piacentini et al, 2011). Likewise, the frequency of the GSTT1 nullgenotype in the Saudi population is 20.1%.…”
Section: Discussioncontrasting
confidence: 45%